Effects of concentrate supplementation on growth, reproduction and milk yield of Black Bengal goats (Capra hircus) (Bangladesh Veterinarian, 2012)
Sixteen female Black Bengal goats (10 ± 0.6 months of age and 11.5 ± 1.3 kg live weight) were divided into four groups having four goats in each. In a completely  randomized design, A, B, C and D were given 150, 200, 250 and 300g concentrate mixture  with ad libitum green grasses. Total dry matter (DM) intake (333.6, 374.7, 416.3 and  456.5g/day in groups A, B, C and D, respectively) was significantly (P